2019
DOI: 10.1007/s00148-018-0726-8
|View full text |Cite
|
Sign up to set email alerts
|

Government Transfers, Work, and Wellbeing: Evidence from the Russian Old-Age Pension

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…Women are seen to improve their well-being substantially as a result of pensions compared to men. Our findings support the similar results achieved by Grogan and Summerfield (2019) in the Russian context. The gender difference in the impact of OAP is as anticipated as the use and meaning of pensions, as with access to and control over other economic resources, is likely to be gendered (Maitra & Ray 2003;Posel et al 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Women are seen to improve their well-being substantially as a result of pensions compared to men. Our findings support the similar results achieved by Grogan and Summerfield (2019) in the Russian context. The gender difference in the impact of OAP is as anticipated as the use and meaning of pensions, as with access to and control over other economic resources, is likely to be gendered (Maitra & Ray 2003;Posel et al 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The results confirm that receiving OAP increases subjective well-being for women and not for men. These results support the findings by Grogan and Summerfield (2019) in the Russian context where OAP was found to increase the wellbeing of women, but not men. The gendered results reflect the societal gender stereotypes where the men derive their worth through their workplace related identity.…”
Section: Robustness Checkssupporting
confidence: 91%
“…Provision of better-quality pension schemes was found to improve the life satisfaction of employees both during and prior to retirement in China ( 25 ). Grogan and Summerfield ( 26 ) found that pension benefits reduced the labor supply of retired female pension subscribers and increased their happiness. Enrollment in pension schemes could help older adults reduce their anxiety and loneliness and promote their self-care capability and life satisfaction ( 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent and significant positive effects of the OAP on the elderly have been found, although there is still a debate regarding gender differences. Kollamparambil and Etinzock (2019) and Grogan and Summerfield (2019) found positive relationships between SWB and OAPs, although they argued that this only applied to elderly females. Bando, Galiani and Gertler (2017) and Galiani, Gertler and Bando (2016) confirmed that OAPs decreased depression among the elderly, thereby increasing their mental well-being.…”
Section: Literature Reviewmentioning
confidence: 99%